Plato’s Theories Reflecting the Adolescent Choice of Social Media as a Main Source for News than Conventional News Outlets - Grace Sri Maria Namora S. (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to demonstrate that a lack of curiosity is a fundamental factor influencing adolescents’ preference for social media over traditional news outlets. To examine this issue, the research employed a mixed-method approach combining quantitative and qualitative data gathered through questionnaires. A total of 30 informants participated and were categorized into two developmental groups: early adolescents aged 12–14 and middle adolescents aged 15–17. The questionnaire explored respondents’ curiosity levels, information-seeking habits, and motivations for choosing certain media platforms. The findings indicate that low curiosity significantly contributes to the preference for social media among early adolescents. At this stage, their interest in deeper information is still limited, making them more inclined toward fast, simple, and entertaining content. However, the hypothesis is less applicable to middle adolescents. Although they also frequently use social media, their media choices are influenced by additional factors such as peer dynamics, a growing sense of autonomy, and broader exposure to information from various sources. This difference suggests that the relationship between curiosity and media preference becomes more complex as adolescents mature. Overall, the study highlights that strategies to encourage critical information-seeking behavior must be tailored to adolescents’ developmental stages.